Typography Design for the Art & Culture Center, Khon Kaen University - Thaworn, Thapthai; Chaturongakul, Kham (Asian Journal of Traditional and Innovative Arts and Textiles, 2023)
This study pertains to the font design for the Art and Cultural Center at Khon Kaen University. Its primary objective is to examine the typographic patterns inherent in the Isan script, drawing insights from Isan art and cultural communication patterns. The study aims to formulate a typeface tailored for the Art and Cultural Center at Khon Kaen University. Additionally, the research endeavors to assess both the typographic characteristics and the usability effectiveness of the developed typeface. The design will encompass three sets of typefaces, each tailored to correspond with the design requirements of the Art and Cultural Center's projects. These three styles include a typeface suitable for formal ceremonial events, characterized by dignified and elegant personalities; a typeface designed for lively and vibrant events, featuring engaging and cheerful characteristics; and a typeface crafted for contemporary art events, embodying a fusion of traditional artistry and international aesthetics. This research constitutes a qualitative study, with key informants comprising three individuals possessing pertinent expertise. These individuals encompass administrators from the Art and Cultural Center, an expert in typography design, a professional in media production within the university, and an expert in Isan culture. The research employs methodologies such as in-depth interviews and design evaluation surveys. The research findings indicate that the assessment results for the font styles (Thai and Roman) by the overall sample group have an average score of 4.40, with a standard deviation of 0.23, a conformity index of 4.40, a percentage score of 73.33, and a font style level at a very high level. Additionally, the data from the evaluation of the usability of the fonts (Thai and Roman) by the overall sample group have an average score of 3.60, a standard deviation of 0.22, a conformity index of 4.80, a percentage score of 80.00, and the font style level is at the highest level.